1983
DOI: 10.1104/pp.72.3.809
|View full text |Cite
|
Sign up to set email alerts
|

An Endogenous α-Amylase Inhibitor in Barley Kernels

Abstract: Barley (Hordeum distichum cv Klages) kernels were shown to contain a factor that converted malted barley a-amylase II to the a-amylase III form. After purification by ammonium sulfate fractionation, ion exchange chromatography on DEAE-Sephacel, and gelfiltration on Bio Gel P60, the factor gave a single band of protein on isoelectric focusing. The purified factor inhibited hydrolysis of soluble starch by a-amylase II from malted barley and germinated wheat (Triticum aestivum cv Neepawa). However, a-amylase I fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 4 publications
(9 reference statements)
1
59
0
Order By: Relevance
“…More recent results (25) have shown that a-amylase III is a mixture of a-amylase II and a low mol wt protein. This may explain the immunochemical identity observed previously between a-amylases II and III (20).…”
Section: Resultsmentioning
confidence: 99%
“…More recent results (25) have shown that a-amylase III is a mixture of a-amylase II and a low mol wt protein. This may explain the immunochemical identity observed previously between a-amylases II and III (20).…”
Section: Resultsmentioning
confidence: 99%
“…One of these soluble seed proteins has recently been identified as an inhibitor of the endogenous barley or-amylase 2 isozyme and of the bacterial protease subtilisin and has been shown by amino acid sequencing to be a member of the soybean trypsin inhibitor (Kunitz) family (11,18,23,24). As with other seed proteins (2), the level of translatable mRNA for this bifunctional inhibitor peaks from 15 to 30 days after anthesis (MUNDY and BRANDT, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary three-dimensional model has been constructed for the closely related wheat a-amylase/subtilisin inhibitor [4]. The strict isoenzyme specificity of BASI in its reactions with barley a-amylases has previously been established, thus BASI reacts with a-amylase 2 or high pI a-amylase (AMY2), but not with the 80% identical isozyme 1 or low pl a-amylase [5][6][7]. The BASI-AMY2 complex is tightly bound at pH 8 and shows a pH optimum more alkaline than that of the AMY2 substrate reaction [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%